Praktik-Praktik Good Governance Pada Koperasi Simpan Pinjam Sari Amertha Dana - Trikajayanti, Ni Komang Ayu; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2021)
In terms of quantity, cooperatives are growing rapidly in Denpasar City, one of which is the Savings and Loans Cooperative (KSP) Sari Amertha Dana in Denpasar City. This cooperative is able to face and get through this pandemic crisis well so that it continues to run normally. Although the COVID-19 pandemic situation caused some members of KSP Sari Amertha Dana to have difficulty paying loans, KSP Sari Amertha Dana continued to run their operations and there were no layoffs. This study aims to identify and analyze the practices of Good Governance (GG) applied to KSP Sari Amertha Dana. This study uses qualitative methods with triangulation techniques and descriptive analysis. The results of the analysis state that the practices of transparency, accountability, responsibility, independence, and equality and fairness carried out by KSP Sari Amertha Dana have been implemented well . Keywords : Transparency; Accountability; Responsibility; Independence; Fairness.